Transformasi Islam Moderat Mohammad Natsir Dalam Bernegara - Sugianto, Sugianto; Aisyah, Umi; Utama, Esen Pramudya; Hidayat, Rahmat (JURNAL JAWI, 2021)
This article aims to reveal the transformation of moderate Islam by Mohammad Natsir in the state. Where Natsir who lives not only as a statesman, but also in Islam is a Muslim thingker and scholar. Movements and upheavals of thought whose source is Islam, makin Natsir a militant fighter and statesmen in the fiht for Islam and the state. The primary sources in this study are: 1) M. Natsir, Fiqhud Da’wah, cet. Ke-10, (Jakarta: Capita Selecta,1996), 2). M. Natsir, Capita Selecta I-III (Bandung: Sumur Bandung, 1961), dan 3), M. Natsir, Islam dan akal merdeka, (Bandung: Sega Arsy, 2015), 4). M. Natsir, Islam sebagai Dasar Negara, (Bandung: Sega Arsy, 2014), dan 5) M. Natsir, Revolusi Indonesia, (Bandung: Sega Arsy, 2016). Next, the date were analyzed using the method content analysis and critical discourse analysis. The result showed that the transformation of moderate Islam by Mohammad Natisr was reflected in Natsir is political style, where Natsir combines the concept of state with religion, Islam as the core in politics. So it can concluded that Natsir’s transformation of moderate Islam in the state uses the concept of an Islamic democration state.